Cryopreservation method and composition of the vitrification solution affect viability of in vitro bovine embryos - Vargas Reyes, José N; Chacón Jaramillo, Liliana (Revista Colombiana de Ciencias Pecuarias, 2016)
an optimal formulation for vitrifying in vitro-produced (IVP) bovine embryos is currently unavailable. Objective: to estimate whether differences in composition of vitrification solutions may affect the viability of IVP embryos as compared to that of embryos cryopreserved by a conventional slow-freezing method. Methods: bovine IVP embryos were cryopreserved by two methods: 1) a slow controlled-rate (1.5 M ethylene glycol (EG)), or 2) vitrification by using two different vitrification and thawing/warming solutions: (1) Protocol V1: commercial vitrification Kit, and (2) Protocol V2: defined vitrification (20% EG; 20% dimethyl sulfoxide (DMSO); 20% fetal bovine serum (FBS)) and warming (20% FBS; 0.2 M sucrose) solutions. Embryo viability was recorded at 24, 48, and 72 h after thawing/warming by evaluating the number of embryos that re-expanded and developed to the hatching blastocyst stage. Results: embryo survival rate was affected by the method of cryopreservation, where the frequency of embryos that re-expanded at 24 h after thawing/warming was higher for embryos vitrified with protocols V1 and V2 (89.0%, 86.2%, respectively) compared to those cryopreserved by the slow-controlled rate method (73.6%, p < 0.05). Similarly, higher percentage of embryos cryopreserved by vitrification hatched at 72 h, where protocol V2 resulted in higher percentage of hatched embryos (84.3%) compared to protocol V1 (64,0%, p < 0.05), and both were higher compared to the slowcontrolled rate method (55.2%, p < 0.05). Conclusions: the method of cryopreservation and composition of the vitrification solution have a direct effect on the viability of bovine IVP embryos.